Vascular effects of oxysterols and oxyphytosterols in apoE −/− mice. Issue 1 (May 2015) - Weingärtner, Oliver; Husche, Constanze; Schött, Hans F.; Speer, Timo; Böhm, Michael; Miller, Charlotte M.; McCarthy, Florence; Plat, Jogchum; Lütjohann, Dieter; Laufs, Ulrich
Abstract Objectives The aim of our study was to investigate vascular effects of oxysterols and oxyphytosterols on reactive oxygen species (ROS), endothelial progenitor cells, endothelial function and atherogenesis. Methods Male apoE−/−mice were treated with cholesterol, sitosterol, 7-ß–OH–cholesterol, 7-ß–OH–sitosterol, or cyclodextrin by daily intraperitoneal application. The respective concentrations in the plasma and in the arterial wall were determined by gas chromatography-flame ionization or mass spectrometry. ROS production was assessed by electron-spin resonance spectroscopy in the aorta, endothelial function of aortic rings and atherosclerosis in the aortic sinus was quantitated after 4 weeks. Results Compared to vehicle, there was no difference in plasma cholesterol levels and arterial wall concentrations after i.p. application of cholesterol. 7-ß–OH–cholesterol concentrations were increased in the plasma (33.7 ± 31.5 vs. 574.57.2 ± 244.92 ng/ml) but not in the arterial wall (60.1 ± 60.1 vs. 59.3 ± 18.2 ng/mg). Sitosterol (3.39 ± 0.96 vs. 8.16 ± 4.11 mg/dL; 0.08 ± 0.04 vs. 0.16 ± 0.07 μg/mg, respectively) and 7-ß–OH–sitosterol concentrations (405.1 ± 151.8 vs. 7497 ± 3223 ng/ml; 0.24 ± 0.13 vs. 16.82 ± 11.58 ng/mg, respectively) increased in the plasma and in the aorta. The i.p-application of the non-oxidized cholesterol or sitosterol did not induce an increase of plasma oxysterols or oxyphytosterols concentrations. Oxidative stress in the aorta was increased in 7-ß–OH–sitosterol treated mice, but not in mice treated with cholesterol, sitosterol, or 7-ß–OH–cholesterol. Moreover, cholesterol, sitosterol, 7-ß–OH–cholesterol, and 7-ß–OH–sitosterol did not affect endothelial-dependent vasodilation, or early atherosclerosis. Conclusion Increased oxyphytosterol concentrations in plasma and arterial wall were associated with increased ROS production in aortic tissue, but did not affect endothelial progenitor cells, endothelial function, or early atherosclerosis.